2021
DOI: 10.1093/jmcb/mjab057
|View full text |Cite
|
Sign up to set email alerts
|

Pyk2 suppresses contextual fear memory in an autophosphorylation-independent manner

Abstract: Clustered protocadherins (Pcdhs) are a large family of cadherin-like cell adhesion proteins that are central for neurite self-avoidance and neuronal connectivity in the brain. Their downstream non-receptor tyrosine kinase Pyk2 (proline-rich tyrosine kinase 2, also known as Ptk2b, Cakb, Raftk, Fak2, and Cadtk) is predominantly expressed in the hippocampus. We constructed Pyk2 null mouse lines and found that these mutant mice showed enhancement in contextual fear memory, without any change in auditory-cued and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Previous studies have found that Npas4, an immediate early gene, is enhanced in Pyk2 knockout mice, but how it Mediators of Inflammation is regulated and its molecular mechanisms remain unclear [84]. Inhibition of Fyn can reduce the expression of inflammatory factors and upregulate the expression of Npas4, which is regulated by Pyk2.…”
Section: Inflammation and Fynmentioning
confidence: 99%
“…Previous studies have found that Npas4, an immediate early gene, is enhanced in Pyk2 knockout mice, but how it Mediators of Inflammation is regulated and its molecular mechanisms remain unclear [84]. Inhibition of Fyn can reduce the expression of inflammatory factors and upregulate the expression of Npas4, which is regulated by Pyk2.…”
Section: Inflammation and Fynmentioning
confidence: 99%
“…Gene editing techniques, acting as a potential therapeutic option, have been widely investigated in treatment of the nuclear genetic diseases over the past decade ( Sharma et al, 2015 ; Nelson et al, 2016 ; De Ravin et al, 2017 ; Zheng et al, 2022 ), with an increasing number of clinical trials ongoing ( Arabi et al, 2022 ). However, its implication in mitochondrial diseases caused by mtDNA mutations has been hampered by the lack of efficient tools to manipulate the mtDNA ( Silva-Pinheiro and Minczuk, 2022 ), with the exception that deleterious mtDNA copies could be cut and eliminated by Zinc finger-fused ( Minczuk et al, 2008 ; Gammage et al, 2014 ; Gammage et al, 2016a ; Gammage et al, 2016b ; Gammage et al, 2018b ) or TALE-fused fokI nuclease ( Bacman et al, 2013 ; Reddy et al, 2015 ; Bacman et al, 2018 ; Pereira et al, 2018 ; Yang et al, 2018 ), as well as the monomeric enzyme based on the TALE system ( Pereira et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%